2022
DOI: 10.4103/mjdrdypu.mjdrdypu_192_22
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Multiple-choice Questions (MCQS) Discussion as a Learning Enhancer in Conventional Lecture Class of Undergraduate Medical Students

Abstract: Context: Multiple Choice Questions (MCQs) are one of the commonly used assessment tools in the field of medical education. A few initiatives have been made to use MCQ tests during classes as a mode of test-enhanced learning. However, there is a lack of enough scientific information regarding the use of MCQs as a learning enhancer. Aims: The present study has been undertaken to analyze the effectiveness of MCQ discussion as a learning tool. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…According to one study, undergraduate students given five MCQs three to four days after attending a lecture significantly improved their ability to answer questions [ 20 ]. Another study found that discussion at the end of lectures was an excellent and effective revision tool [ 21 ]. Faculty development programs have also focused on improving MCQ item quality to enhance student's overall competency levels during yearly academic assessments [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to one study, undergraduate students given five MCQs three to four days after attending a lecture significantly improved their ability to answer questions [ 20 ]. Another study found that discussion at the end of lectures was an excellent and effective revision tool [ 21 ]. Faculty development programs have also focused on improving MCQ item quality to enhance student's overall competency levels during yearly academic assessments [ 22 ].…”
Section: Introductionmentioning
confidence: 99%